PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT KARYABERA PERDANA JAYA BOJONGSARI - Iwadh Syawqi; Priehadi Dhasa Eka (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to determine the effect of leadership style and work motivation on employee performance at PT. Karyabera Perdana Jaya Bojongsari. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 65 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are leadership has a significant effect on employee performance with a determination coefficient value of 57.6% and the hypothesis test obtained t count> t table or (5.503> 2.000). Work motivation has a significant effect on employee performance with a determination coefficient value of 55.4% and the hypothesis test obtained t count> t table or (8.440> 2.000). Leadership and work motivation simultaneously have a significant effect on employee performance with a regression equation Y = 9.423 + 0.176X1 + 0.589X2. The determination coefficient value is 57.6% while the remaining 42.4% is influenced by other factors. The hypothesis test yielded a calculated F value > F table, or (42.146 > 2.751).